An Analysis of Students’ Difficulties in Learning Mathematics on the Topic of Least Common Multiple (LCM) in Class A/1, Cohort 2023 - Ayu Winda Rajagukguk; Fiber Yun Almanda Ginting; Anna Mariani (Pustaka Karya Mandiri, 2025)
This study aims to analyze students’ learning difficulties in mastering the topic of Least Common Multiple (LCM) in Mathematics course in Class A/1, Cohort 2023. This research employs a qualitative descriptive method. Data were collected through tests, interviews, and documentation involving students who experienced difficulties in understanding LCM material. The results show that students face difficulties in understanding the basic concept of LCM, selecting and applying solution methods, performing calculations, and solving word problems. The causes of learning difficulties are internal factors such as lack of prerequisite knowledge, mathematics anxiety, and low self-confidence, as well as external factors such as monotonous teaching methods, lack of instructional media, and limited independent practice. The strategies to overcome these difficulties include the use of concrete and visual learning media, step-by-step exercises, collaborative learning, contextual learning, and direct feedback from lecturers. The findings of this study are expected to contribute to improving the quality of mathematics learning in higher education.